2009
DOI: 10.1080/00365510903007000
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume, an indicator of platelet activation, is increased in patients with mitral stenosis and sinus rhythm

Abstract: Systemic thromboembolism is a serious major complication in patients with mitral stenosis. However, the pathogenesis of thromboembolism in mitral stenosis is not fully understood. Previous studies have demonstrated that platelet activation occurs in serum of patients with rheumatic mitral stenosis (MS). The aim of this study was to assess the mean platelet volume (MPV), an indicator of platelet activation, in patients with MS. The study group consisted of 36 patients with MS who were in sinus rhythm. An age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…These thrombocytes express excessively PDGF, thromboxane A 2 , glycoprotein Ib and IIb/IIIa receptors. 10 The production of these substances increases thrombosis in patients with cancer and especially, high level of PDGF may promote tumor growth and invasion in malignancies. 11 In the literature, MPV was reported as a prognostic factor for different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…These thrombocytes express excessively PDGF, thromboxane A 2 , glycoprotein Ib and IIb/IIIa receptors. 10 The production of these substances increases thrombosis in patients with cancer and especially, high level of PDGF may promote tumor growth and invasion in malignancies. 11 In the literature, MPV was reported as a prognostic factor for different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the “giant platelets” have a higher enzymatic activity and produce more thromboxane A2 [14]. Also MPV is associated with myocardial infarction, acute cerebral ischemia and transient ischemic attack (TIA) [4, 15]. Increased values of MPV were observed in patients with mitral stenosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] An association between stenosis and platelet activation has been observed in other groups of valvular heart disease. Varol et al 24 showed that MPV was significantly elevated in patients with mitral stenosis and sinus rhythm compared to the controls. Mitral valve stenosis represents a relatively low-gradient stenosis, whereas AS is a high-gradient valvular defect.…”
Section: Discussionmentioning
confidence: 98%